Most Recent Data (1999). Statistics Canada. CANSIM: International Trade - Merchandise Exports | Country: Canada | Province: Nunavut | Table: Interprovincial and international trade flows at producer prices | Variable: Accommodation services and meals (x 1,000,000), International exports | Units: $CAD, 1999. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. Dataset-ID: 075-001-130. - Statistics Canada (Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc., 2015)
Statistics Canada (2015). CANSIM: International Trade - Merchandise Exports | Country: Canada | Province: Nunavut | Table: Interprovincial and international trade flows at producer prices | Variable: Accommodation services and meals (x 1,000,000), International exports | Units: $CAD, 1999. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. [Data-file]. Dataset-ID: 075-001-130. Dataset: Provides statistics on goods grown, extracted, produced, or manufactured in Canada and subsequently sold abroad, referred to as “domestic exports.” Also included are goods of foreign origin that have entered the country to be consumed but are subsequently sold to another country without any substantial transformation, termed “re-exports.” Domestic exports and re-exports include goods that were exported, as well as their values, quantities, mode of transport, province of origin, and country of destination. CANSIM is Statistics Canada's key socioeconomic database. The datasets included here provide statistics on the Canadian population, and the nation’s resources, economy, society, and culture. In addition to conducting a Census every five years, approximately 350 active surveys are conducted on virtually all aspects of Canadian life. Statistics are provided for the nation as a whole, provinces, and other subnational geographies where available. Category: International Relations and Trade Source: Statistics Canada Established as Canada's central statistical office by the Statistics Act of 1985, Statistics Canada is required to "collect, compile, analyse, abstract and publish statistical information relating to the commercial, industrial, financial, social, economic and general activities and conditions of the people of Canada." Its main objectives are to provide statistical information and analysis about Canada’s economic and social structure and to promote sound statistical standards and practices. http://www.statcan.gc.ca/ Subject: Exports, Merchandise, International Trade